Respuesta :

Answer: 6x+3y=12

x=-1/2y+2

Step-by-step explanation:

step 1: add -3y to both sides

6x+3y+-3y=12+-3y

6x=-3y+12

step 2: divide both sides by 6

6x/6=-3y+12/6

Answer:

y = 6 and x = -1.

Step-by-step explanation:

It's normally useful for me to rewrite the equation so they match. I'm using the substitution method.

First find out what "y" equals (I'm using the second equation):

Add 8 to both sides:

y - 8 = 2x

  +8    +8

y = 2x + 8

Plug this into the previous equation.

6x + 3(2x + 8) = 12

Distribute first:

3(2x + 8)

3 * 2x = 6x

3 * 8 = 24

6x + 24

Rewrite the equation:

6x + 6x + 24 = 12

Find liked terms.

6x + 6x + 24 = 12

They are liked terms so combined them: 6x + 6x = 12x.

Rewrite the equation again:

12x + 24 = 12

Solve for "x".

Subtract 24 on both sides.

12x + 24 = 12

      -24   -24

12x = -12

Divide 12 to get x by itself.

12x = -12

    12

x = -1

Plug x into the second equation to find y.

y - 8 = 2(-1)

y - 8 = -2

Add 8 to both sides.

y - 8 = -2

  +8   +8

  y = 6

The answers are y = 6 and x = -1.